Combining Cryogel Architecture and Macromolecular Crowding‐Enhanced Extracellular Matrix Cues to Mimic the Bone Marrow Niche. Issue 1 (10th January 2023) - Martínez‐Vidal, Laura; Magno, Valentina; Welzel, Petra B.; Friedrichs, Jens; Bornhäuser, Martin; Werner, Carsten
Abstract : Back Cover : In article number 2200348, Carsten Werner and co‐workers report on the development of a three‐dimensional bone marrow niche model that closely mimics the natural architecture of trabecular bone and the extracellular stromal compartment. The multiphasic scaffolds are based on polymeric cryogels and decellularized human extracellular matrix secreted in situ in the presence of macromolecular crowders.